Effect of radiation exposure on survival after first solid cancer diagnosis in A-bomb survivors - Sposto, Richard; Sugiyama, Hiromi; Tsuruyama, Tatsuaki; Brenner, Alina V. (Cancer Epidemiology, 2023)
Comparison of the estimated effect of atomic bomb radiation exposure on solid cancer incidence and solid cancer mortality in the RERF Life Span Study (LSS) reveals a difference in the magnitude and shape of the excess relative risk dose response. A possible contributing factor to this difference is pre-diagnosis radiation effect on post-diagnosis survival. Pre-diagnosis radiation exposure theoretically could influence post-diagnosis survival by affecting the genetic makeup and possibly aggressiveness of cancer, or by compromising tolerance for aggressive treatment for cancer. We analyze the radiation effect on post-diagnosis survival in 20,463 LSS subjects diagnosed with first-primary solid cancer between 1958 and 2009 with particular attention to whether death was caused by the first-primary cancer, other cancer, or non-cancer diseases. From multivariable Cox regression analysis of cause-specific survival, the excess hazard at 1 Gy (EH1Gy) for death from the first primary cancer was not significantly different from zero – p = 0.23, EH1Gy = 0.038 (95 % CI: −0.023, 0.104). Death from other cancer and death from non-cancer diseases both were significantly associated with radiation dose: other cancer EH1Gy = 0.38 (95 % CI: 0.24, 0.53); non-cancer EH1Gy = 0.24 (95 % CI: 0.13, 0.36), both p < 0.001. There is no detectable large effect of pre-diagnosis radiation exposure on post-diagnosis death from the first primary cancer in A-bomb survivors. A direct effect of pre-diagnosis radiation exposure on cancer prognosis is ruled out as an explanation for the difference in incidence and mortality dose response in A-bomb survivors. •Analysis of survival of 20,000 + atomic bomb survivors diagnosed with solid cancer.•A-bomb radiation exposure prior to a cancer diagnosis does not influence survival from the primary diagnosed cancer.•A-bomb radiation exposure prior to cancer diagnosis does influence survival for non-primary cancer death causes.•Radiation influence on solid cancer prognosis does not contribute to the difference in mortality and incidence dose response.